PENGARUH KOMITMEN ORGANISASI DAN KOMPETENSI KARYAWAN TERHADAP KINERJA KARYAWAN PADA KANTOR DIREKSI PT. PERTANI (PERSERO) MEDAN - MARKUS DODDY SIMANJUNTAK (JURNAL ILMIAH KOHESI, 2020)
Human resources are needed by companies in carrying out company activities. Because without human resources as the driving force of the company, the company cannot run as it should. Generally organizational commitment is the degree to which an employee identifies himself with a particular organization and its objectives and wishes to maintain its membership in the organization. Competence is an ability for a job or task based on skills and knowledge and is supported by the work attitude required by the job. This study aims to analyze and determine the effect of organizational commitment and employee competence on employee performance at the office of the Directors of PT. Pertani (Persero) Medan. This study uses 2 independent variables, namely organizational commitment and employee competence on employee performance. Data analysis methods used in this study are validity, reliability, classic assumption test, multiple linear analysis, t test, F test and coefficient of determination. The data used are primary data and secondary data. The number of samples in this study were 70 people. Data processing is performed using SPSS 20.0 for Windows. Based on the results of multiple linear regression tests, it can be concluded that the employee competency variable is the variable that most influences on employee performance, where the coefficient value is 0.815. Based on the results of the t test that have been carried out, it is obtained that the variable of organizational commitment and employee competence has a positive and partially significant effect on employee performance. From these results it is concluded that all alternative hypotheses are accepted. Based on the F test results, the calculated F value of 125.812 with a significance level of 0.000, while the F value of the table at alpha 5% is 2.50. Therefore F arithmetic> F table and the significance level of 0,000 <0.05 shows that organizational commitment and employee competencies together are positive and significant effect on employee performance. Based on the determination coefficient test results obtained that the contribution of the value of organizational commitment and employee competence is 79% while 21% is the contribution of other variables not included in this study.